Penyebab Terjadinya Perceraian Di Pengadilan Agama Kota Gorontalo - Daud, Aditya Pratama; Junus, Nirwan; Sarson, Mohamad Taufiq Zulfikr (CV. ITTC INDONESIA, 2023)
Abstract Divorce is the end point of a marriage that is unable to achieve the noble goal of family happiness as expected by every married couple. The phenomenon of divorce due to increasing economic factors has recently intrigued the author to conduct research on divorce due to economic factors at the Religious Court of Gorontalo City in 2021. The purpose of this study is to explore and find out data about the basic concept of divorce, to find out what factors are happening at the Religious Courts of Gorontalo City in 2021, and to find out the description of divorce due to economic factors and the impact of these factors on divorce in Gorontalo City in 2021 2021. This research uses a normative approach because it highlights the number of divorces due to certain factors. While the method uses a descriptive method because it uses a description to describe the data presented. The results of this study indicate that divorce is the breaking of the marriage bond for certain reasons in accordance with religious rules and marriage laws. There are 13 factors that cause divorce in Indramayu Regency, namely unhealthy polygamy, moral crisis, jealousy, forced marriage, economy, no responsibility, underage marriage, persecution, being punished, biological defects, politics, third party interference. , and there is no harmony. Of the many factors, it turns out that economic factors dominate the divorce rate in Gorontalo City in 2021. In 2021 there were 5550 cases of divorce with 13 factors causing divorce, including divorce due to economic factors as many as 4905 cases or around 88.38%, the remaining 11 .62% ​​for factors other than economics. The percentage of divorces due to economic factors shows the magnitude of the economic influence on household integrity. Therefore, family income (economic) which is a very important matter for husbands and wives to pay attention to, turns out to have a huge impact on the occurrence of divorce in Gorontalo City in 2021.